**1**

**- ---- q - 7 = - 3**

**3**

. + 7 + 7

**1**

**- ---- q = 4**

**3**

3 3

×(- —) ×( - —)

1 1

**q = - 12**-1 over 3q-7=-3

Tutors, sign in to answer this question.

. + 7 + 7

3 3

×(- —) ×( - —)

1 1

Hi Alexis;

-1 over 3q-7=-3

This is...

-1/(3q-7)=-3

First, let's eliminate the complicated fractions.

We will multiply both sides by (3q-7)...

(3q-7)[-1/(3q-7)]=-3(3q-7)

Let's cancel where appropriate...

(3q-7)[-1/(3q-7)]=-3(3q-7)

-1=-3(3q-7)

Let's divide both sides by -3...

-1/-3=[-3(3q-7)]/-3

1/3=3q-7

Let's add 7 to both sides...

7+1/3=3q-7+7

7 1/3=3q

Because 7 1/3=22/3...

22/3=3q

Let's multiply both sides by 1/3 to achieve the isolation of q...

(22/3)(1/3)=3q(1/3)

22/9=q

Let's check our work...

The original equation was...

-1/(3q-7)=-3

-1/[3(22/9)-7]=-3

-1/[(22/3)-7]=-3

Because 7=21/3

-1/[(22/3)-(21/3)]=-3

-1/(1/3)=-3

Because dividing by 1/3 is equal to multiplying by 3...

-1(3)=-3

-3=-3

First - multiply both sides of the equation by the bottom portion of the fraction (3q-7) to eliminate the fraction.

Next - you are left with -1=-9q+21

Then - treat it like a normal equation. Subtract 21 from both sides to get -22=-9q

Finally - divide both sides by -9, and you find that q = 22/9. (or "22 over 9")

Good luck!

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

## Comments

(-1 over3)q-7=-3 or (-1/3)q - 7 = -3